2009
DOI: 10.1007/s10439-009-9711-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid III ATD in Inverted Impacts: Influence of Impact Angle on Neck Injury Risk Assessment

Abstract: -The purpose of this paper is to present a protocol of inverted drop-tests using a 50 th percentile Hybrid III Anthropomorphic Test Device (ATD) and investigate the influence of angle and velocity at impact on neck injury risk assessment. The tests were based on existing cadaveric experimental protocols for inverted seated positions. In this study selected ATD impact orientations were also assessed in both the sagittal and coronal planes. Twenty-six tests were performed at impact velocities from 1.4 m.s -1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, no study was found in literature that has investigated its biofidelity under direct impact loading, such as in inverted drop tests. Therefore, the Hybrid III neck was employed in this work as its behaviour under direct loading has been addressed in several studies [13,21,28]; in addition, it was available within the consortium. Using human body surrogates whose neck can better reproduce the behaviour of the human neck under axial loading would probably modify the calculated value of γ m , but would not modify its concept, which is the main idea of the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study was found in literature that has investigated its biofidelity under direct impact loading, such as in inverted drop tests. Therefore, the Hybrid III neck was employed in this work as its behaviour under direct loading has been addressed in several studies [13,21,28]; in addition, it was available within the consortium. Using human body surrogates whose neck can better reproduce the behaviour of the human neck under axial loading would probably modify the calculated value of γ m , but would not modify its concept, which is the main idea of the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…Using a neck was necessary to measure the neck tensile force, the indicator of BSF, but the Hybrid III neck is known for its low fidelity particularly under head axial loading [62,63]. However this is not the load condition of interest in the present paper.…”
Section: Resultsmentioning
confidence: 99%
“…Using the standing Hybrid III allowed the head, torso and legs of the ATD to be aligned and minimized the influence of legs on neck loads observed in previous head-first ATD impact experiments. 7 However, as discussed, small variations in ATD posture after release were not assessed and could have influenced the neck loads. Using more instrumentation, particularly the lower neck load cell, could provide more insight into better understanding foam pit response in future testing.…”
Section: Discussionmentioning
confidence: 99%